The Relation Between Early Mobilization and Wound Healing Process of Patients After Laparotomy at Royal Prima Hospital, Medan, from 2020 to 2024 - Aisyah Mughni Muchtar; Yeni Puspawani; Yolanda Eliza Putri Lubis (International Journal of Health and Pharmaceutical (IJHP), 2025)
An incision in the abdominal wall is made during laparatomy, a significant surgical surgery, and the healing duration for this incision can vary. Patients should engage in early mobilization, or physical activity to increase blood circulation and decrease the risk of problems, right after surgery. This can hasten the healing process of wounds. The purpose of this research is to find out how early mobilization affects wound healing, pain levels, and hospital stay duration for patients at Royal Prima Hospital Medan who have undergone a laparotomy. Using a cross-sectional design, this study employed quantitative analytical methods. Patients who underwent a laparotomy between 2020 and 2024 made up the study's population. Using inclusion and exclusion criteria, a convenience sample of 35 individuals was chosen. The data was examined using the ChiSquare test, which was derived from patient medical records. Early mobilization was performed by the majority of patients (91.4%), and 88.6% of those patients had satisfactory wound healing. "Significant relationships between early mobilization and wound healing (p = 0.000), pain severity (p = 0.003), and length of hospital stay (p = 0.018) were shown by statistical tests. It is evident that early mobilization is crucial for patients to experience faster wound healing, less pain, and a shorter hospital stay following laparotomy. In conclusion, patients' wound healing processes are significantly improved by early mobilization following laparotomy. The goal of healthcare providers is to educate patients and routinely practice early mobilization in order to hasten healing and avoid complications after surgery.